Social Quality Measurement and Perceived Social Quality: The Case of Peshawar, Pakistan. Issue 1 (1st June 2019) - Ali, Muhammad Yasir; Lin, Ka
Abstract : This study investigates the difference between the maps of social quality and perceived social quality. Using survey data collected from Peshawar, a prominent city in Pakistan, we compare the general and the perceived maps of social quality drawn from survey respondents based on their stands of income, education, age, and gender. With this comparison, the study conducts the regression analysis about the data to reveal the relations between these factors and draw some policy implications. The analysis contrasting objective and subjective visions of the social quality map may support a constructionist view on social quality and, more essentially, bring our view into the diversity of the perceived maps of social quality in reference to the interests of different social groups in society.